2022
DOI: 10.1111/cup.14196
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of the oncofetal protein IMP3 is helpful in the diagnosis of intravascular large B‐cell lymphoma using skin biopsy

Abstract: Background The oncofetal protein insulin‐like growth factor 2 mRNA binding protein‐3 (IMP3) is expressed in various cancers. In this study, we examined the diagnostic utility of IMP3 immunohistochemistry in the context of intravascular large B‐cell lymphoma (IVL). Methods We obtained 25 skin biopsy (SB) specimens diagnosed as IVL and nine IVL‐negative SB specimens from 27 IVL patients. Additionally, 27 negative SB specimens from 26 non‐IVL patients were obtained from our pathology archives. We performed IMP3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…14,31 However, despite its diagnostic difficulty, no IHC marker has been previously reported to differentiate IVLBCL from reactive B cells. The present study demonstrated that all 111 samples of IVLBCL expressed IMP3, and combined with the results of the previous study, 22 all 136 pathology specimens diagnosed with IVLBCL were positive for IMP3. Moreover, IMP3 highlighted cells suspicious for IVLBCL in 26.8% (11/41) of pathological specimens obtained from IVLBCL patients, which were diagnosed as negative for IVLBCL in routine practice.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…14,31 However, despite its diagnostic difficulty, no IHC marker has been previously reported to differentiate IVLBCL from reactive B cells. The present study demonstrated that all 111 samples of IVLBCL expressed IMP3, and combined with the results of the previous study, 22 all 136 pathology specimens diagnosed with IVLBCL were positive for IMP3. Moreover, IMP3 highlighted cells suspicious for IVLBCL in 26.8% (11/41) of pathological specimens obtained from IVLBCL patients, which were diagnosed as negative for IVLBCL in routine practice.…”
Section: Discussionsupporting
confidence: 88%
“…Using a single institutional cohort, we performed immunohistochemistry (IHC) for IMP3 on skin biopsies and found IMP3 to be a highly sensitive marker for IVLBCL in skin biopsies. 22 Considering that the clinical presentation and diagnosis of IVLBCL are not limited to the skin, we sought to expand on these findings to capture the full clinical and pathological presentation of IVLBCL. Here, we used a multi-institutional cohort to analyze the utility of IMP3 IHC in the diagnosis of IVLBCL in various organs and validated it using double staining with paired box 5 (PAX5).…”
mentioning
confidence: 99%
See 1 more Smart Citation